Evaluating Public Private Partnership (PPP) Contracts For Service Delivery By Kalangala Infrastructure Services Limited In Kalangala District, Uganda - Niwabiine , Andrew (Archives of Business Research, 2019)
The paper evaluates performance of an Implementation Agreement of 16th, January, 2009 between Kalangala Infrastructure Services Limited (KIS) and government of Uganda, regarding Ferry Operations between Bukakata and Luku Landing Sites across Lake Victoria, for the benefit of people of Kalangala District. The objective of the study was to establish whether key stakeholders who have been left out in the agreement can have their concerns addressed; and, whether KIS which monitors and evaluates itself in the project can provide the right quality of service to intended beneficiaries. Purposive and simple Random methods were applied on a sample of 105 correspondents selected from a population of 125 stakeholders using a case study design. Opinions were built basing on data from interviewing and document review. A Qualitative analysis of findings indicated lack of consultation, participation and feedback to key stakeholders. It was also established that stakeholders were denied a chance to and evaluate the project by KIS appointing &paying its own monitor. Based on the above the project fell short of transparency, accountability and value for money. The study recommended a holistic approach involving community participation across the project cycle to ensure service quality, value for money, ownership and sustainability.